2019
DOI: 10.1212/01.wnl.0000580888.56349.3a
|View full text |Cite
|
Sign up to set email alerts
|

Estimated age of first exposure to American football and outcome from concussion

Abstract: ObjectiveTo examine the association between estimated age of first exposure (eAFE) to American football and clinical measures throughout recovery following concussion.BackgroundIn collegiate football players, we reported no association between eAFE and baseline neurocognitive function. It is possible that neurocognitive deficits from earlier eAFE to American football, if present, are sufficiently compensated for in otherwise healthy individuals, but when faced with concussion, earlier eAFE may associate with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…One limitation of our study was that career duration was based on participant’s self-reported eAFE to collision sports. This approach, though, is consistent with that of previous eAFE studies investigating similar populations, 11-14,25 as well as studies of older/retired athletes. 25,44,47,48 We were also unable to verify that individuals participated in collision sports continuously from the age that they self-reported, but as both institutions were sponsored NCAA Division I intercollegiate athletic programs, it is highly likely that this approach is accurate, as lengthy breaks in participation would be quite unusual.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…One limitation of our study was that career duration was based on participant’s self-reported eAFE to collision sports. This approach, though, is consistent with that of previous eAFE studies investigating similar populations, 11-14,25 as well as studies of older/retired athletes. 25,44,47,48 We were also unable to verify that individuals participated in collision sports continuously from the age that they self-reported, but as both institutions were sponsored NCAA Division I intercollegiate athletic programs, it is highly likely that this approach is accurate, as lengthy breaks in participation would be quite unusual.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, we determined career duration by subtracting the participant's eAFE from his age at the time of testing, as done in the eAFE literature. [11][12][13][14] Despite the difference in career duration metrics between testing sites, the results were not significantly different when each site was analyzed independently. In addition to career duration and/or eAFE, participants had to self-report the number of diagnosed concussions sustained before testing.…”
Section: Career Durationmentioning
confidence: 86%
See 3 more Smart Citations